Gumbo for the soul III : males of color share their stories, meditations, affirmation, and inspirations - Wright, Brian L.; Bryan, Nathaniel (College teacher); Sewell, Christopher J. P.; Yates, Lucian, III; Robinson, Michael A. (Educator); Thomas, Kianga (Contemporary perspectives on multicultural gifted education., 2019)
This book for, about, and by Males of Color, amplifies triumphs and successes while documenting trials and tribulations that are instructive, inspiring, and praiseworthy. This book will be a must-read for every Male of Color.